Effects of Anthocyanin and Flavanol Compounds on Lipid Metabolism and Adipose Tissue Associated Systemic Inflammation in Diet-Induced Obesity - Roel A. van der Heijden; Martine C. Morrison; Fareeba Sheedfar; Petra Mulder; Marijke Schreurs; Pascal P. H. Hommelberg; Marten H. Hofker; Casper Schalkwijk; Robert Kleemann; Uwe J. F. Tietge; Debby P. Y. Koonen; Peter Heeringa (Mediators of Inflammation)
Background. Naturally occurring substances from the flavanol and anthocyanin family of polyphenols have been proposed to exert beneficial effects in the course of obesity. We hypothesized that their effects on attenuating obesity-induced dyslipidemia as well as the associated inflammatory sequelae especially have health-promoting potential. Methods. Male C57BL/6J mice (n=52) received a control low-fat diet (LFD; 10 kcal% fat) for 6 weeks followed by 24 weeks of either LFD (n=13) or high-fat diet (HFD; 45 kcal% fat; n=13) or HFD supplemented with 0.1% w/w of the flavanol compound epicatechin (HFD+E; n=13) or an anthocyanin-rich bilberry extract (HFD+B; n=13). Energy substrate utilization was determined by indirect calorimetry in a subset of mice following the dietary switch and at the end of the experiment. Blood samples were collected at baseline and at 3 days and 4, 12, and 20 weeks after dietary switch and analyzed for systemic lipids and proinflammatory cytokines. Adipose tissue (AT) histopathology and inflammatory gene expression as well as hepatic lipid content were analyzed after sacrifice. Results. The switch from a LFD to a HFD lowered the respiratory exchange ratio and increased plasma cholesterol and hepatic lipid content. These changes were not attenuated by HFD+E or HFD+B. Furthermore, the polyphenol compounds could not prevent HFD-induced systemic rise of TNF-α levels. Interestingly, a significant reduction in Tnf gene expression in HFD+B mice was observed in the AT. Furthermore, HFD+B, but not HFD+E, significantly prevented the early upregulation of circulating neutrophil chemoattractant mKC. However, no differences in AT histopathology were observed between the HFD types. Conclusion. Supplementation of HFD with an anthocyanin-rich bilberry extract but not with the flavanol epicatechin may exert beneficial effects on the systemic early inflammatory response associated with diet-induced obesity. These systemic effects were transient and not observed after prolongation of HFD-feeding (24 weeks). On the tissue level, long-term treatment with bilberry attenuated TNF-α expression in adipose tissue.